2007
DOI: 10.1016/j.febslet.2007.07.042
|View full text |Cite
|
Sign up to set email alerts
|

A single Gly114Arg mutation stabilizes the hexameric subunit assembly and changes the substrate specificity of halo‐archaeal nucleoside diphosphate kinase

Abstract: Nucleoside diphosphate kinase from extremely halophilic archaeon (HsNDK) requires above 2 M NaCl concentration for in vitro refolding. Here an attempt was made to isolate mutations that allow HsNDK to refold in low salt media. Such a screening resulted in isolation of an HsNDK mutant, Gly114Arg, which efficiently refolded in the presence of 1 M NaCl. This mutant, unlike the wild type enzyme, was expressed in Escherichia coli as an active form. The residue 114 is in close proximity to Glu155 of the neighboring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…On the contrary, G114R mutant recently isolated efficiently refolded in the presence of 1 M NaCl, in which the wild-type HsNDK showed marginal refolding; i.e., G114R mutation made the enzyme less dependent on salt concentration for refolding. The residue 114 of the mutant is in close proximity to Glu155 of the neighboring subunit in the three-dimensional hexameric structure of HsNDK [6,7]. We thus speculated that the attractive electrostatic interactions occur between Arg114 and Glu155 in the mutant HsNDK hexamer, and stabilize the subunit assembly of this mutant protein in low salt.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…On the contrary, G114R mutant recently isolated efficiently refolded in the presence of 1 M NaCl, in which the wild-type HsNDK showed marginal refolding; i.e., G114R mutation made the enzyme less dependent on salt concentration for refolding. The residue 114 of the mutant is in close proximity to Glu155 of the neighboring subunit in the three-dimensional hexameric structure of HsNDK [6,7]. We thus speculated that the attractive electrostatic interactions occur between Arg114 and Glu155 in the mutant HsNDK hexamer, and stabilize the subunit assembly of this mutant protein in low salt.…”
Section: Introductionmentioning
confidence: 93%
“…We have previously reported that mutation of G114R results in about 10 • C higher thermal stability than the wild-type HsNDK [7]. Thermal stability was therefore examined in 0.2 M NaCl by measuring the resistance to heat treatment at 20-60 • C. Fig.…”
Section: Stability Of Quaternary Structure In Low Saltmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of natural NDK sequence variants, with an extreme case being the P. aerophilum NDK (Fig. 1), where this residue is replaced by a 10-amino-acid insert, which also affects the substrate specificity (17). Interestingly, a randomly generated G3R mutant of the archaeal H. salinarum NDK (67% GϩC) also resulted in an increase in the enzyme affinity for pyrimidine nucleotides (35), thus confirming the critical role of this amino acid for substrate specificity.…”
Section: Resultsmentioning
confidence: 99%
“…4.1). Furthermore, it resulted in about 10 • C higher thermal stability in a low-salt solution than that of the parent molecule (Ishibashi et al, 2007). We thus speculated that the attractive electrostatic interactions occurred between Arg114 and Glu155 in G114R mutant and were reduced to the extent that the subunit assembly of this mutant protein can occur in low salt.…”
Section: Generation Of Low-salt Stable Extreme-halophilic Proteinsmentioning
confidence: 99%